1994
DOI: 10.1021/ma00079a031
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hydrogen bonding in cellulose-synthetic polymer blend systems with regioselectively substituted methylcellulose

Abstract: Specifically substituted O-methylcelluloses, 2,3-di-O-methylcellulose and 6-O-methylcellulose (parts B and C of Figure 1, respectively), were used as cellulosic components in blends with poly (ethylene oxide) (PEO) and poly(vinyl alcohol) (PVA). Since their hydroxyl groups (OH) form controlled intraand intermolecular hydrogen bonds, the cellulose derivatives are useful as model compounds to investigate the effect of hydrogen bonding in cellulose-synthetic polymer blend systems. FTIR (Fourier transform infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(107 citation statements)
references
References 3 publications
5
100
1
1
Order By: Relevance
“…Hydroxyl groups in C2, C3 and C6 contribute to the formation of various kinds of inter-and intra-molecular hydrogen bonds. The formation of inter-and intra-molecular hydrogen bonds in the cellulose not only has a strong influence on the physical properties of cellulose, including solubility [7][8], hydroxyl reactivity [9][10] and crystallinity [11][12], but also plays an important role in the mechanical properties of the cellulose [13]. Calculated by Tashiro and Kobayashi [14] showed that hydrogen bonds contribute about 20% the strain energy to the cellulose.…”
Section: Hydrogen Bonds Analysis Of Natural Celluloses By Using Ftirmentioning
confidence: 99%
“…Hydroxyl groups in C2, C3 and C6 contribute to the formation of various kinds of inter-and intra-molecular hydrogen bonds. The formation of inter-and intra-molecular hydrogen bonds in the cellulose not only has a strong influence on the physical properties of cellulose, including solubility [7][8], hydroxyl reactivity [9][10] and crystallinity [11][12], but also plays an important role in the mechanical properties of the cellulose [13]. Calculated by Tashiro and Kobayashi [14] showed that hydrogen bonds contribute about 20% the strain energy to the cellulose.…”
Section: Hydrogen Bonds Analysis Of Natural Celluloses By Using Ftirmentioning
confidence: 99%
“…Numerous investigations regarding the miscibility in multicomponent polymer systems have been reported. Among them, the polymer blends between biopolymers and synthetic polymers are of particular significance as they could be used as biomedical and biodegradable materials [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In the cellulose/PVA blends, two types of hydrogen bonds were reported (22). Then we investigated what kind of intermolecular interaction is present in the r-Ch/PVA blends by means of FT-IR spectrophotometry.…”
Section: Intermolecular Interaction In Regeneratedmentioning
confidence: 99%